(untitled) (Globalization and Business, 2018)
This work deals with the objective prerequisites for the origin of the “new neoclassical synthesis” which is in the pro- cess of formation, goals, tasks; the need to use this new trend in the country’s economic policy is justified. An explanation is given to the organic linkage of the pub- lic sector economics with the “new neoclassical synthesis” and its role in the formation of viable economic policy. The reflection of the main directions of the functioning public sector economics the country’s economic policy is a new challenge to modern civilization. This must be reflected in the “new neo- classical synthesis” which adds novelty to the “neoclassical synthesis” that was successfully used in economic policy of the US and other developed countries in the 1980s. A great contribution in its creation belongs to the author of the first textbook in economics Paul Samuelson.